2005
DOI: 10.1111/j.1365-2036.2006.02756.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of 4‐ and 7‐day triple therapy with rabeprazole, high‐dose levofloxacin and tinidazole rescue treatment for Helicobacter pylori eradication

Abstract: SUMMARY BackgroundHelicobacter pylori treatment failure is becoming an emergent problem in clinical practice. Shorter treatment duration should improve compliance to therapy and keep an acceptable H. pylori eradication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
0
15
0
2
Order By: Relevance
“…18 The minimal duration of treatment was 7 days with a significant lowering of efficacy when a 4-day regimen was used. 19 The efficacy of levofloxacin-based quadruple therapy in this study was within this range. This suggested that the addition of bismuth subcitrate to levofloxacin triple therapy did not improve the efficacy significantly.…”
Section: Discussionmentioning
confidence: 52%
“…18 The minimal duration of treatment was 7 days with a significant lowering of efficacy when a 4-day regimen was used. 19 The efficacy of levofloxacin-based quadruple therapy in this study was within this range. This suggested that the addition of bismuth subcitrate to levofloxacin triple therapy did not improve the efficacy significantly.…”
Section: Discussionmentioning
confidence: 52%
“…-prescribed in our study could have contributed to this relatively high figure. Although the experience with this last dose of levofloxacin is limited, 19,22,52,53 and no study has directly compared low and high-doses of this drug in the same protocol, we chose the higher dose with the aim to increase the likelihood of cure (obviously, further studies are necessary before the low or the high levofloxacin dose is recommended). Nevertheless, in a recent systematic review, incidence of adverse effects, and severe adverse effects in particular, with levofloxacin-based therapies was 18% and 3%, 18 which are in accordance with our results.…”
mentioning
confidence: 99%
“…Thus, no severe side‐effects were reported in our study (although mild to moderate adverse effects were reported by 36% of the patients; it is conceivable that the high dose of levofloxacin – 500 mg b.i.d. – prescribed in our study could have contributed to this relatively high figure); although the experience with this last dose of levofloxacin is very limited [25–27], and no study has directly compared low and high doses of this drug in the same protocol, we chose the higher dose with the aim to increase the eradication rate. In the previously mentioned systematic review, adverse effects were severe in only 3% of the patients treated with levofloxacin‐containing therapies [11].…”
Section: Discussionmentioning
confidence: 99%